IPV outcomes from gPM+ intervention - Hidrobo, Melissa; Alderman, Harold; Deyessa, Negussie; Gilligan, Daniel O.; Kalva, Parthu; Leight, Jessica; Mulford, Michael; Workie, Abaydar (2023)
Melissa Hidrobo, Harold Alderman, Negussie Deyessa, Dan Gilligan, Parthu Kalva, Jessica Leight, Michael Mulford, and Abaydar Workie REGIONAL WORKSHOP SPIR II Learning Event Co-organized by IFPRI, USAID, CARE, ORDA, and World Vision MAY 16, 2023 - 9:00AM TO MAY 17, 2023 - 5:00PM EAT